2021
DOI: 10.1371/journal.ppat.1009843
|View full text |Cite
|
Sign up to set email alerts
|

Hantavirus infection-induced B cell activation elevates free light chains levels in circulation

Abstract: In humans, orthohantaviruses can cause hemorrhagic fever with renal syndrome (HFRS) or hantavirus pulmonary syndrome (HPS). An earlier study reported that acute Andes virus HPS caused a massive and transient elevation in the number of circulating plasmablasts with specificity towards both viral and host antigens suggestive of polyclonal B cell activation. Immunoglobulins (Igs), produced by different B cell populations, comprise heavy and light chains; however, a certain amount of free light chains (FLCs) is co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 40 publications
0
7
0
1
Order By: Relevance
“…This is contrary to what has been reported for infections with Sin Nombre orthohantavirus [ 40 ], which causes a different disease phenotype (HCPS) with a different organ targeting (lungs instead of kidneys). Interestingly, our previous results have shown that severe NE patients have higher circulating free light chain levels [ 41 ], which are considered as markers of polyclonal B cell activation and increased total humoral responses. This serves as a speculative support for the observed higher neutralizing antibody levels, being part of a general increase in antibody production in severe NE cases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is contrary to what has been reported for infections with Sin Nombre orthohantavirus [ 40 ], which causes a different disease phenotype (HCPS) with a different organ targeting (lungs instead of kidneys). Interestingly, our previous results have shown that severe NE patients have higher circulating free light chain levels [ 41 ], which are considered as markers of polyclonal B cell activation and increased total humoral responses. This serves as a speculative support for the observed higher neutralizing antibody levels, being part of a general increase in antibody production in severe NE cases.…”
Section: Discussionmentioning
confidence: 99%
“…This serves as a speculative support for the observed higher neutralizing antibody levels, being part of a general increase in antibody production in severe NE cases. Importantly, while similarly upregulated, free light chains do not correlate with disease severity in acute HCPS [ 41 ], further suggesting variable pathogenic mechanisms between the two orthohantaviral diseases in which increased humoral response might be contributing to NE (and HFRS) pathogenesis, whereas HCPS would be dominated by direct virus infection-related mechanisms. It should be noted that this lower level of eGFR in patients with higher NAb is likely not due to immunocomplex deposition in kidneys since previous works on the matter had shown no evidence of such complexes by immunofluorescence methods in kidney biopsies [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Human CD8 T-cell response in PUUV infection occurs after the acute phase and, curiously, is associated with boosting of EBV-specific CD8 memory T-cells and transient presence of EBV DNA in some patients, indicative of viral reactivation [ 36 ]. These findings may be because EBV is a polyclonal B-cell activator and can also explain the following findings in PUUV infection: nonrelated toxoid immunity in PUUV infection (tetanus-specific and pertussis-specific IgG as well as T-cells) [ 37 ], the free immunoglobulin light chains in hantavirus infection [ 38 ], and the observed [ 39 ] increased risk (73%) for lymphoma (resembling mononucleosis-associated Hodgkin lymphoma) after PUUV HFRS.…”
Section: Role Of Different Factors In the Variationmentioning
confidence: 99%
“…Serum FLC levels are also affected by viral infections. Previous studies have shown that serum levels of κ and λ FLCs are significantly increased in acute hantavirus diseases [ 10 ]. Additionally, notable elevations in serum κ and λ FLC levels have been observed in severe cases of SARS-CoV-2-infected patients [ 11 ].…”
Section: Introductionmentioning
confidence: 99%